Potential of Adora2b as an immunotherapeutic target for gastric cancer - Li, Jie; Shi, Ruixin; Zhang, Xinyao; Guo, Zhijuan; Ji, Ru (Frontiers in Immunology, 2025)
Gastric cancer (GC) is characterized by highly heterogeneous tumors, whose progression is genetically driven and closely associated with hypoxia and an immunosuppressive tumor microenvironment (TME). Hypoxia accelerates adenosine accumulation, activates the low-affinity Adora2b receptor, weakens antitumor immunity, and promotes metastasis. Adora2b is lowly expressed in normal gastric mucosa. Still, it is significantly upregulated in diseased tissues, where it is widely expressed in various immune cells and the tumor stroma, mediating immune escape, fibrosis, and vascular remodeling. This review summarizes the cell-type-specific signaling mechanisms of Adora2b in the TME (e.g., T cells, macrophages) and, drawing on research in other tumors, proposes mechanistic explanations for its tissue-specific roles. Based on existing evidence, Adora2b regulates epithelial-mesenchymal transition (EMT) in GC cells via the cAMP/PKA/Snail pathway, and preclinical studies show that targeting Adora2b reduces the migration and invasion of GC cells. These findings suggest that targeting Adora2b may provide new insights for gastric cancer therapy.